2024
DOI: 10.1186/s12951-023-02259-6
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and assessment of therapeutic cargo in engineered exosomes: a systematic review

Zhen Chen,
Min Xiong,
Jiaqi Tian
et al.

Abstract: Exosomes are nanoscale extracellular vesicles secreted by cells and enclosed by a lipid bilayer membrane containing various biologically active cargoes such as proteins, lipids, and nucleic acids. Engineered exosomes generated through genetic modification of parent cells show promise as drug delivery vehicles, and they have been demonstrated to have great therapeutic potential for treating cancer, cardiovascular, neurological, and immune diseases, but systematic knowledge is lacking regarding optimization of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 127 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…They have excellent stability with a long half-life in the bloodstream and can be easily taken up by cells [ 55 , 56 ]. Additionally, their nanoscale size allows them to traverse blood-ocular barriers effectively [ 57 ]. Exosomes can be administered through vitreous cavity to reach the inner and outer retinal layers, or through peribulbar or retrobulbar regions across the ocular walls, providing a safer and more efficient drug delivery method compared to systemic intravenous injection [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have excellent stability with a long half-life in the bloodstream and can be easily taken up by cells [ 55 , 56 ]. Additionally, their nanoscale size allows them to traverse blood-ocular barriers effectively [ 57 ]. Exosomes can be administered through vitreous cavity to reach the inner and outer retinal layers, or through peribulbar or retrobulbar regions across the ocular walls, providing a safer and more efficient drug delivery method compared to systemic intravenous injection [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As research progresses, the limitations of utilizing natural sEVs for treating ischemic stroke are becoming increasingly evident, specifically in their inadequate targeting capabilities and content loading. 101 , 102 Several approaches have been devised to rectify these limitations and enhance the targeting, stability, and loading capacity of NSC-sEVs. These modifications together fall under the category of engineered NSC-sEVs.…”
Section: Using Engineered Sevs For Treating Ischemic Strokementioning
confidence: 99%
“…This makes them a good candidate for oral drug delivery. Numerous studies have investigated the loading techniques of plant-derived EVs with nucleic acids and have shown that EVs can protect loaded nucleic acids from enzymatic degradation and deliver them in an intact and functional form [ 113 , 114 ]. Techniques used for plant EV loading include electroporation, which causes transient pore formation and allows nucleic acid entrance into EVs; sonication of EVs in the presence of nucleic acids to alter membrane structures; passive nucleic acid internalization in the presence of appropriate salt, pH, and temperature conditions; and mechanically (extrusion techniques) or chemically increased membrane permeability to allow nucleic acids entrance.…”
Section: Edible Plant-derived Evs As a Platform For Mucosal Vaccine D...mentioning
confidence: 99%
“…Techniques used for plant EV loading include electroporation, which causes transient pore formation and allows nucleic acid entrance into EVs; sonication of EVs in the presence of nucleic acids to alter membrane structures; passive nucleic acid internalization in the presence of appropriate salt, pH, and temperature conditions; and mechanically (extrusion techniques) or chemically increased membrane permeability to allow nucleic acids entrance. The efficacy of these techniques varies depending on the EV source and the nucleic acid type [ 113 ].…”
Section: Edible Plant-derived Evs As a Platform For Mucosal Vaccine D...mentioning
confidence: 99%